RECONFIGURING ISLAMIC DISCOURSE ON RELIGIOUS FREEDOM AND THE RIGHTS OR RELIGIOUS MINORITIES: Progressive Muslim Perspective - Yusdani, Yusdani (Universitas Islam Indonesia, 2017)
Religion as a doctrine of God that guides human life is often accused of having ‘failed’ to protect the noble values of humanity. This can be seen with the onset of war and humanitarian conflicts in the name of religion. Consequently, religion is suspected to be only used as a tool to legitimize the actions of people to achieve all desires. Therefore, religion is regarded as outdated teachings for humanity. The question that arises is where man must seek the truth to protect noble human values? In search of answers of this question, in terms of absolutism and relativism of truth, no doubt that religion is an absolute truth because it comes from the Absolute. However, along the way, the revelation of God who has come down to man through His messengers has undergone distortion and reduction of meaning. Distortion and reduction of meaning was one of the factors that gave birth to a variety of interpretations, including those that are intolerant and exclusive. Therefore, to find the truth of the revelation of God that guarantees the protection of humans and humanity in these religions, one needs to explore the principles and values contained in substantial religious scriptures. In closing off the overall discussion of this paper, it can be stated that there is urgency in the context of Islam today, including in Indonesia, to formulate a set of Islamic values that can be an alternative and solution for the creation of a just society that respects human values. Therefore, an Islamic reason formulation needs to be developed in the context of human life in accordance with a global ethics such as democracy, pluralism, and human rights. As such, the development of Islamic thought today needs to accommodate the values of equality, justice, and humanity. Thus, the position of all citizen is equal and the rights of religious minorities must be guaranteed and protected equally and fairly. Keywords : Contemporary Society, Progressive Ijtihadists, Minority Rights, Global Ethics.